Last edited by mr fantastic; Jul 27th 2010 at 02:21 PM. Reason: Re-titled.
Follow Math Help Forum on Facebook and Google+
Originally Posted by fxs12 Use Google to fnd the sum of cubes of formula. Now apply that formula.
1^3+2^3+3^3+...+n^3=(1^2+2^2+3^2+...+n^2)^2={(n(n+ 1)/2}^2 Someway to prove the formula: An^4+Bn^3+Cn^2+Dn+E=S_n put: n=1,2,3,4 and solve the system of 4 equations, find A,B,C,D,E.
Hello, fxs12! How about an inductive proof? . . . True. . . .[1] . . . . . . . . . . . . Therefore, [1] becomes: . The inductive proof is complete.
View Tag Cloud